The adoption of Fintech using technology for better security, speed, and customer experience in finance - Hasan Jafar, Syed; Kannan, Hemachandran 1985-; Akhtar, Shakeb; Parvez Alam Khan; El-Chaarani, Hani (Routledge, 2024)
"The term FinTech is a combination of the words "financial" and "technology," which is now a real business need. However, there are limited books covering holistic aspects from adoption to the future of FinTech. This book directs readers on how to adopt FinTech, develop regulation and risk frameworks, implement it in financial services, address ethical dilemmas, and sustain improvements. The anticipated challenges are developing trust, security, privacy, and a regulated environment without compromising profitability and financial stability. The anticipated solution is strengthening the governance, use of unbreachable technologies, risk management, consumer data protection, and sustainable practices. This book will be recommended to every stakeholder, especially FinTech scholars, practices, and policymakers. This book will provide holistic insight and opportunities to support FinTech developments for the betterment of the economy and society. FinTech is defined as injecting technology into the area of finance for better security, speed, and customer experience. This book provides readers with direct case studies for better understanding. In addition, it explains regulation and usage of FinTech in daily transactions. Readers are shown how FinTech has an imperative role in financial analysis, Insurtech, and the share market"--
2406
Keywords: Technische Innovation; Technischer Fortschritt; Schlüsseltechnologie; Finanzdienstleistungsmarkt; Finanzmarketing; Fintech; Financial services industry / Technological innovations; Aufsatzsammlung